问题
解答题
(1)(a2)3-(a2)4÷(-a2)5
(2)(x3)4+(x2)6
(3)(-2a2b3)4+(-a)8-(2b4)3
(4)(0.125)2006-(-8)2007-(-1)2006
(5)(p-q)4÷(q-p)3-(p-q)2
(6)4-(-2)-2-32÷(3.14-π)0.
答案
(1)(a2)3•(a2)4÷(-a2)5
=a6•a8÷(-a10)
=a14÷(-a10)
=-a4;
(2)(x3)4+(x2)6
=x12+x12=2x12;
(3)(-2a2b3)4+(-a)8•(2b4)3
=16a8b12+8a8b12=24a8b12;
(4)(0.125)2006•(-8)2007•(-1)2006
=(
)2006•(-8)2006•(-8)•11 8
=[
×(-8)]2006•(-8)1 8
=(-1)2006•(-8)
=-8;
(5)(p-q)4÷(q-p)3•(p-q)2
=(p-q)4÷[-(p-q)3]•(p-q)2
=-(p-q)4-3+2
=-(p-q)3
=(q-p)2;
(6)4-(-2)-2-32÷(3.14-π)0
=4-
-9÷11 4
=4-
-91 4
=-5
.1 4